KEPRIBADIAN NASABAH MEMPENGARUHI ADOPSI DAN PENGGUNAAN SALURAN PERBANKAN HIJAU - Purnama Sari, Desak Made Febri; Putri Adnyani, I Gusti Ayu Yogi (EconBank: Journal of Economics and Banking, 2023)
The customer's personality influences the adoption and use of green banking channels. The purpose of this research is to determine the effect of customer personality on the use of green banking channels through the adoption of BCA and BRI Bank customers who are domiciled in Denpasar City. In this study, quantitative data was used to collect information by giving questionnaires to participants. Customers of Bank BCA and Bank BRI who are domiciled in Denpasar City are the research samples. The number of samples in this study were 102 respondents using purposive sampling method. Based on the results of this study, customer personality has a positive and significant effect on adoption, adoption has a positive and significant effect on the use of green banking channels, personality has a positive and significant effect on the use of green banking channels and customer personality has a positive and significant effect on the use of green banking channels through adoption. The findings of this study are where the customer's personality accepts the adoption of innovation in the use of bank products with the concept of green banking channels at Bank BCA and Bank BRI in Denpasar City.